BLEEDING EFFICIENCY AND KEEPING QUALITY IN BROILER CHICKEN MEAT SUBJECTED TO TWO SLAUGHTERING METHODS - SABOW, AZAD B.; MAJEED, SHAREHAN J. (Journal of Duhok University, 2020)
The effects of traditional slaughter in comparison with decapitation on bleeding efficiency and shelf life of broiler breast meat during three days postmortem of aging were evaluated. Twenty male broiler chickens were subjected to either traditional slaughter or decapitation. The bleeding efficiency was determined in terms of blood loss and residual hemoglobin and myoglobin concentration in breast muscle while the shelf life of breast meat was performed through microbiological analysis and lipid oxidation. The results indicate no differences (p>0.05) in bleeding efficiency, microbiological quality and oxidative stability between the two methods. However, increased lipid oxidation and growth of microorganisms with storage time was observed in breast meat samples from both slaughter groups. In conclusion, slaughtering broiler chicken following traditional or decapitation procedure did not affect blood lost or residual blood and keeping quality of broiler breast meat.